2015
DOI: 10.1111/jcpt.12287
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib for the treatment of mild-to-moderate depression due to acute brucellosis: a double-blind, placebo-controlled, randomized trial

Abstract: Celecoxib is a safe and effective treatment for depression due to brucellosis when compared with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…A recent clinical study has shown beneficial effects of anti-inflammatory co-medication with antidepressants in depressed patients with increased levels of peripheral inflammation [16]. This is in line with a study by Raison et al [9] who performed a proof-of-concept study with a TNF antagonist in patients with TRD and showed improvement in patients with high baseline inflammatory biomarkers.…”
Section: Discussionsupporting
confidence: 78%
“…A recent clinical study has shown beneficial effects of anti-inflammatory co-medication with antidepressants in depressed patients with increased levels of peripheral inflammation [16]. This is in line with a study by Raison et al [9] who performed a proof-of-concept study with a TNF antagonist in patients with TRD and showed improvement in patients with high baseline inflammatory biomarkers.…”
Section: Discussionsupporting
confidence: 78%
“…). We identified 39 studies covering 44 RCTs with a total of 10 891 individuals: 14 trials ( N = 4451) studied NSAIDs [five add‐ons , eight monotherapy except one trial where 45% of patients were on antidepressant medication ], 12 ( N = 3868) studied cytokine inhibitors [all as monotherapy except for one study where 62% of the patients were treated with antidepressants ], 9 ( N = 2118) studied statins [three add‐ons and six monotherapy ], 3 ( N = 119) studied pioglitazone as add‐on , 3 ( N = 162) studied minocycline [two add‐ons and one monotherapy ], and 3 ( N = 173) studied glucocorticoids as monotherapy . Of these, eight RCTs could not be included since we did not have access to the necessary data, neither published or after contact to the authors.…”
Section: Resultsmentioning
confidence: 99%
“…The HDRS contains 17 questions (on a 3-point or 5-point scale) that assess severity of depressive symptoms. This scale has been applied in many clinical trials in Iran exploring depression therapeutic efficacy [27][28][29][30][31][32]. The primary outcome measure of this trial was to evaluate efficacy of saffron compared to fluoxetine in improving depressive symptoms in postpartum individuals using general linear model repeated measures.…”
Section: Outcomementioning
confidence: 99%